Analisis Komparatif Kinerja Sistem Kasir Digital UMKM Menggunakan Metrik Kinerja Web - Putri, Yessica Mega; Munandar, Agus (Syntax Literate, 2025)
The transformation of the small and medium enterprises (SMEs) sector in Indonesia has experienced significant development. Business operators are highly dependent on digital point-of-sale (POS) systems to facilitate transactions and financial management. Researchers compared six prominent digital POS platforms (Majoo, Moka POS, Olsera, Qasir, Pawoon, and Kasir Pintar) using web.dev performance metrics from Google. A comparative descriptive analysis approach with purposive sampling technique was employed based on criteria of operating for at least 3 years, having a minimum of 50,000 active SME users, availability in both website and mobile versions, and achieving a minimum rating of 4.0. Platform evaluation was conducted based on four main metrics: performance, accessibility, best practices, and SEO metrics. Test results showed that Moka POS achieved the highest score with an average of 90.75% on the website and 85.25% on mobile, followed by Kasir Pintar with superior mobile performance. The study found that while most platforms displayed higher website performance than mobile, performance metrics were consistently the aspect with the lowest results across all platforms. The web performance metrics-based evaluation is expected to assist SMEs in selecting digital point-of-sale (POS) systems that satisfy their operational needs and provide recommendations for the professional development of industry practitioners.